Analisis Kelayakan Finansial Rencana Pembangunan Hotel Siliwangi - Fikry Sjaf, Rijalul; Azhar, Moh (Jurnal Ilmiah Rekayasa Sipil, 2024)
As development progresses in the city of Depok, many of vacant land are being marketed in commercial locations. Land which is in a strategic location makes investors interested in buying the land to be developed into a more profitable commercial building. One of the lands being offered is on Jalan Siliwangi, Depok City, with a land area of ​​4410 m2. This research aims to analyze the financial feasibility of the project if a commercial building is built on the vacant land. The analysis was carried out using technical economic analysis integrated with the Highest and Best Use (HBU) analysis method. By knowing the financial feasibility of the project development plan, investors get earlier information regarding whether or not it is feasible to purchase land and project construction at the research object location. Based on The results of the economic analysis of indicator techniques will determine the financial feasibility of building construction projects such as Net Present Value (NPV), Internal Rate of Return (IRR), Payback Period (PP), so the use of Hotels provides the most benefits compared to Offices and Shophouse Complexes. With this level IRR=10.063% > Interest rate 9.311%, which means the project is feasible and can be implemented, then the NPV is >0 (Rp. 7,628,369,872) and the Profitability Index level is 1,060>1. Pay back period 9.2 years (9 years and 2 months).